THE ORIGINS AND EVOLUTION OF SOCIAL PROTECTION SYSTEMS WORLDWIDE - Abdulkhayev Saidullo (International Scientific and Current Research Conferences, 2025)
This article looks at the historical roots and gradual growth of social protection systems in different societies and times. Social protection refers to a collection of institutional strategies designed to shield individuals and groups from social vulnerabilities, including poverty, illness, unemployment, disability, and aging. Utilizing a historical and comparative framework, the study delineates the progression of social protection from primitive communal support systems and philanthropic traditions to contemporary state-sponsored welfare frameworks. The analysis shows that social protection has changed over time because of changes in politics, the economy, and how people think about social justice and human rights. The results show that social protection mechanisms have been around for a long time and are still changing, and they are becoming more important for dealing with today's global problems.